IDENTIFICATION OF CagA HARBORING HELICOBACTER PYLORI FROM BUCCAL SWAB COLLECTED FROM TOBACCO ADDICTED WOMEN SUBJECTS - SMRITIKANA BISWAS,; DIBYENDU BHOWMICK,; CHANDRADIPA GHOSH, (International Journal of Pharma and Bio Sciences, 2013)
Helicobacter pylori is recognized as the major etiological agent of chronic gastritis, gastric adenocarcinoma and lymphoma. The present study was carried out to investigate the presence of Helicobacter pylori in buccal salivary sample collected from tobacco addicted women from India and to study certain virulence properties including detection of the presence of cancer producing gene cagA. Here, sixteen bacterial isolates were identified as Helicobacter pylori and they were different in their colony morphology i.e., rugose (37.5%), opaque (62.5%). All of them were motile, protease positive, highly biofilm forming. All of them were found resistant to chloramphenicol, tetracycline but sensitive to ampicillin and kanamycin. But, resistance was found to amoxicillin, trimethoprim and streptomycin for 50%, 25% and 12.5% isolates, respectively. PCR analysis revealed five isolates to possess cagA gene. Results of the present study predicted that these Helicobacter pylori isolates may be a potential threat for developing gastric infection in future.